Unveiling the wind energy future of Türkiye with policies technologies and potential - Haci Sogukpinar; Ismail Bozkurt; Saadin Oyucu; Ahmet Aksoz (Heliyon)
Türkiye has set ambitious renewable energy targets aligned with the European Union Green Deal, aiming for 55 % renewables by 2035 and finally, zero-emission by 2050 so for this target a total installed capacity of 120 GW in wind and solar energy by 2035. In line with Türkiye's target of 120 GW of installed power in wind and solar energy by 2035, the sector aims to invest 5 GW of wind annually. This target will ensure that all wind investments to be put into operation in Türkiye by 2035 will reach a total of 50 GW and the wind-generated electricity will reach 138 TW-hours per year. As of the end of 2024, the total installed power has reached 13 GW and new installations continue rapidly. The wind potential of Türkiye is 118,683 MWe for wind speeds of over 6.8 m/s at a height of 50 m and the total WEP (Wind Energy Potential) of Türkiye is 48,000 MWe for regions with wind speeds of over 7 m/s. Offshore wind potential is calculated as 17,393 MWe, and these data are excluded from the land wind potential. Preparations for offshore wind power plants are ongoing, with an installation target of 5000 MWe for 2035. This study reviews Türkiye's wind energy potential, the evolution of its installations, and the policies driving this growth, concluding with recommendations for achieving its ambitious targets.